Preclinical Studies of Euphorbia lactea Aerial Extract on Atherogenic-Diet-Induced Atherosclerosis - Khan, Zubair; Siddiqui, Nazia; Agarwal, Garima; Chaudhary, Anurag; Ali, Syed Salman; El-Shorbagi, Abdel-Nasser; Chaudhary, Sachin; Tripathi, Prabhash Nath (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Atherosclerosis is a complex progressive pathological process that produces lesions in the inner wall of an artery because of the abnormal lipid metabolism, and dysregulation of inflammatory processes. Increased levels of Low-Density Lipoprotein (LDL) and Total Cholesterol (TC) lead to hyperlipidaemia which is a major risk factor for atherosclerosis. Materials and Methods This research comprises the assessment of hydro-alcoholic extract of the aerial part of Euphorbia lactea on high-fat diet-induced atherosclerosis in rats. The hydroalcoholic extract with doses (200 and 400 mg/kg body mass, p.o.) was assessed for hypolipidaemic activity. The blood samples were collected in heparinized tubes at the end of the experiment, and then centrifuged and collected the supernatant to determine Triglyceride (TG), High-Density Lipoprotein (HDL), LDL, TC, and Very Low-Density Lipoprotein (VLDL). The atherosclerotic markers including Creatine Phosphokinase (CPK), Alanine Transaminase (ALT), Alkaline Phosphatase (ALP), Lactate Dehydrogenase (LDH), and Aspartate Transaminase (AST) section of heart aorta were examined by histopathology. Results The results exhibited significantly reduced TG, LDL, TC, and VLDL levels. However, the HDL level was significantly increased as compared with induced rats. This current research demonstrated the anti-atherogenic potential of hydroalcoholic extract of the aerial part of E. lactea. Conclusion Overall, the results revealed that plant extract at different doses lowered LDL and TC levels significantly. Hence it could be used to benefit from atherosclerosis and its associated risk factors inclusive of heart attack, and stroke. Furthermore, it might be used as a traditional medicine against CVD and beneficial in the treatment of hyperlipidemia-induced atherosclerosis and diabetes mellitus.
Keywords: Atherosclerosis; High-fat diet; Hypolipidemic; E. lactea; Heart attack; Stroke